THE EFFECT OF READ, ASK, PARAPHRASE (RAP) STRATEGY ON STUDENTS’ COMPREHENSION IN READING NARRATIVE TEXT AT THE ELEVENTH GRADE OF SMK SWASTA PUTRA JAYA STABAT - Novi Indriani; Nudia Yultisa; Lilis Saputri (Jurnal Serunai Bahasa Inggris, 2022)
The objective of the study is to know the significant effect of using RAP Strategy on Students’ Comprehension in Reading Narrative Text at the Eleventh Grade of SMK Swasta Putra Jaya Stabat. The strategy used in this study was a quantitative method using quasi-experimental. Two classes were taken as the sample of the study with 35 students in each class. The classes were designed as an experimental class and a controlled class. The experimental class was taught by implementing Read, Ask, Paraphrase (RAP) strategy while the controlled class was taught without using conventional method. The students’ population at the are SMK Swasta Putra Jaya Stabat 105 students, and the samples were 70 students (35 students for experimental class and 35 students for controlled class). The sampling technique that used was random sampling. Moreover, this research was conducted through the following procedures: giving pre-test, applying treatments and giving post-test. The data analyzed in this research was gained through multiple choice. The result of the conclusion that in testing the hypothesis, the value of Rcount>alpha. Has been known the alpha is 0,05, then  0,0718 > 0,05. It concluded the hypothesis is accepted, so it can be concluded that treatment with Read, Ask, Paraphrase (RAP) strategy on Students’ Comprehension at the Eleventh Grade of Smk Swasta Putra Jaya Stabat.